What is talked about? Community living staff experiences of talking with older people with intellectual disability about dying and death. (21st July 2013) - Wiese, M.; Stancliffe, R. J.; Dew, A.; Balandin, S.; Howarth, G.
Abstract Background The aim of this study was to explore what community living staff talked about and did with people with intellectual disability (ID) to assist them to understand dying and death. Method Guided by grounded theory methodology, focus groups and one‐to‐one interviews were conducted with 22 staff who had talked about any topic relating to dying and death with their clients. Results There was little evidence that staff talked with, or did things with clients to assist understanding of the end of life, both prior to and after a death. Prior to death staff assisted clients in a limited way to understand about determining wishes in preparation for death, and what dying looks like by observance of its passage. Following a death staff offered limited assistance to clients to understand the immutability of death, and how the dead can be honoured with ritual, and remembered. Conclusions The findings have implications for why people with ID have only partial understanding of the end of life, the staff skills required to support clients' understanding, and when conversations about the end of life should occur.